Isolation and genetic characterization of mutans streptococci associated with dental caries in rural field practice of a dental institution: In vivo study - B Santosh Kumar; H Indiresha Narayana; B V Sreenivasa Murthy; Sylvia Mathew; P Damodhar; S S Shantha Kumar (Wolters Kluwer Medknow Publications, 2019)
Background: Streptococcus mutans is well-known causative microorganism in the development of dental caries because they drop the plaque pH and produce acids from carbohydrates and survive in the acidic environment. It is now evident that knowledge of the bacteria enforces empirical approach to therapy, then specific antimicrobial therapy that might allow more conservative treatment options. Over the past few decades, there has been a remarkable increase in the prevalence rate of dental caries among children and the elders. Genotypic methods help in the detection and manipulation of nucleic acids which allows microbial genes to be examined directly. Aim: The aim of this study is to isolate and characterize S. mutans from rural population and to obtain genomic DNA and screen DNA band pattern. Methodology: A total of 80 plaque samples were collected from the buccal surfaces of maxillary and lingual surfaces of mandibular first molar with carious teeth in patients at a rural outreach center in Chikkaballapur district, Karnataka. Among these, 48 clinical isolates of S. mutans were recovered. Further, genomic DNA was extracted from all the positively isolated strains including the standard strain (microbial type culture collection 497), and stored at 4°C in tris EDTA buffer (TE). To analyze the molecular heterogeneity of the clinical strains, polymerase chain reaction (PCR), and restriction fragment length polymorphism was performed using restriction enzymes Hind III and Hae III. Using agarose gel electrophoresis, genomic DNA band pattern was analyzed. Results: Statistically significant difference was seen in the "dex" gene collected from sample DNA and standard DNA in three different parameters (S. mutans 497). Conclusion: Genomic DNA of S. mutans was successfully isolated from the rural population. Dex gene was successfully amplified using PCR. Hae III enzymes successfully digested PCR amplicons and the fragments exhibited visible heterogeneity.